Does formal knowledge search depth benefit Chinese firms' innovation performance? Effects of network centrality, structural holes, and knowledge tacitness. Issue 1 (2nd January 2017) - Ruan, Aijun; Chen, Jin
Abstract : Accessing external knowledge is an important factor in successful innovation. Knowledge search is an issue of concern for Chinese firms because many firms generally have relatively weak research and development (R&D) and innovation capabilities that cannot support innovative development through mere internal innovations. This study examines the interactive effects of network centrality, structural holes, and knowledge tacitness when formal knowledge search depth (FKSD) affects innovation performance from the perspective of formal/informal knowledge search. A survey of 161 firms in China suggests that FKSD positively affects innovation performance, and the effect is positively moderated by network centrality. Given high knowledge tacitness, FKSD is more effective in fostering innovation performance when firms' network centrality is higher. Furthermore, high knowledge tacitness results in rich structural holes negatively moderating the effect of FKSD on innovation performance, whereas low tacitness generates a positive moderating role. This indicates that Chinese firms may consider using more formal search channels to increase external knowledge search depth and to dynamically adjust the depth of such a formal search or the mode of network structural embeddedness according to the degree of knowledge tacitness.